Sensitivity Reliability Analysis of Power Distribution Networks Using Fuzzy Logic - Wadi, Mohammed; ELMASRY, WİSAM; Küçük, İsmail; Shahinzadeh, Hossein (Institute of Electrical and Electronics Engineers Inc., 2022)
This paper proposes a combined method utilizing both the reliability block diagram analytical technique and the Monte Carlo simulation method to estimate the reliability of power systems. Since the reliability of collected data is associated with noise and erroneous data, performing the sensitivity analysis is indispensable. Sensitivity analysis utilizing fuzzy logic specifies these uncertainties and their effects on the reliability calculations. The proposed method is applied to the Roy Billiton Test System Bus-2 to confirm its applicability. The obtained results have verified the sensitivity analysis's importance in drawing an accurate picture of reliability evaluation and a crucial tool for distribution power utilities to identify the susceptible parameters that seriously erode the system's complete reliability. © 2022 IEEE.
2022 12th International Conference on Computer and Knowledge Engineering, ICCKE 2022
Keywords: Fuzzy Logic; Monte Carlo Simulation; Power Distribution Networks; Reliability; Reliability Block Diagram; Roy Billiton Test System; Sensitivity Analysis